Engaging Employees at Work: Insights From India. Issue 1 (February 2018) - Gupta, Manish
The Problem: The engagement literature suffers not only from inconsistent construct conceptualizations but also from the paucity of research in India, a country whose employment conditions differ substantially from those of the Western nations. Therefore, there is a need to have clarity on the contribution of the engagement construct to the field of human resource development (HRD) and examine the significance of engaging employees in India. The Solution: To address the aforementioned research gaps, the objectives of this issue are to derive a clear understanding of the engagement construct and to gain fresh insights into the antecedents and consequences of engagement at work, particularly in the context of India. The Stakeholders: This issue is expected to benefit researchers, HRD professionals, and organizations by identifying the strongest engagement predictor of employee performance, suggesting several ways of engaging workforce in India, and providing fresh insights into the nomological network of engagement at work.